2004
DOI: 10.3201/eid1012.040459
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Lyssavirus Infection in Bats, Cambodia

Abstract: In Cambodia, 1,303 bats of 16 species were tested for lyssavirus. No lyssavirus nucleocapsid was detected in 1,283 brains tested by immunofluorescence assay. Antibodies against lyssaviruses were detected by enzyme-linked immunosorbent assay in 144 (14.7%) of 981 serum samples. Thirty of 187 serum samples contained neutralizing antibodies against different lyssaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 10 publications
4
33
0
2
Order By: Relevance
“…It is noteworthy that half of these cases involved included people with regular close contact with bats including bat handlers. Interestingly, several studies involving bats from different Asian countries have shown evidence of virus neutralizing antibodies against rabiesrelated viruses (most commonly ABLV) in up to 19 % of the samples tested (Arguin et al, 2002;Reynes et al, 2004;Lumlertdacha et al, 2005). Although the majority of human rabies cases in the world are reported from Asian countries no evidence has been reported for infection with rabies related viruses in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that half of these cases involved included people with regular close contact with bats including bat handlers. Interestingly, several studies involving bats from different Asian countries have shown evidence of virus neutralizing antibodies against rabiesrelated viruses (most commonly ABLV) in up to 19 % of the samples tested (Arguin et al, 2002;Reynes et al, 2004;Lumlertdacha et al, 2005). Although the majority of human rabies cases in the world are reported from Asian countries no evidence has been reported for infection with rabies related viruses in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Improved surveillance across the continent is required to fully appreciate the epidemiology of these viruses. In addition, serological evidence of predominantly ABLV infection in bats from several Asian countries and WCBV in bats collected in Kenya (with only known isolate from Asia) predicts a more widespread distribution of these viruses than may have been anticipated (Arguin et al, 2002;Reynes et al, 2004;Lumlerthdacha et al, 2005;Kuzmin et al,2008c).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is possible that bats develop persistent EBLV infection, manifested as the long-term carriage of viral RNA without overt disease. In particular, some wild-caught bats have antibody to EBLV for up to 3 years, and viral RNA has been detected in the tissues of apparently healthy bats (14,31,36,40), although it is also possible that bats experience an unapparent acute infection and are subject to continual reinfection.…”
mentioning
confidence: 99%
“…Bats have been known as reservoir for rabies virus for a long time [1]. Recently, Research in several countries around of Indonesia such as Vietnam, Cambodia, Thailand and Philippines reported that high level of rabies virus exposure in bats population in its region happened [2,3,4,5]. Bats have also been considered as natural hosts of many common human and animal viruses, such as measles, mumps, parainfluenza, canine distemper and hepatitis C viruses [6,7].…”
Section: Introductionmentioning
confidence: 99%